Morphology and description of infraciliary bands pattern in four Metadinium Awerinzew & Mutafowa, 1914 species (Ciliophora, Entodiniomorphida, Ophryoscolecidae) with taxonomic notes on the genus - Cedrola, Franciane; Rossi, Mariana Fonseca; Martinele, Isabel; D’agosto, Marta; Dias, Roberto Júnio Pedroso (Zootaxa, 2018)
The genus Metadinium includes ophryoscolecid ciliates, with two retractile ciliary zones in the anterior body portion, two broad skeletal plates, a lobed macronucleus and two contractile vacuoles. Species belonging to this genus were recorded in several geographical locations and in different host species. However, they were mostly described based on a single ciliatological technique, and until now, there is only one description of the infraciliary pattern in Metadinium ciliates (Metadinium medium). The present study performs the morphological and infraciliature characterization of four species belonging to Metadinium: M. esalqum, M. minorum, M. rotundatum and M. ypsilon; and presents taxonomic notes on the genus. The oral infraciliature in these four Metadinium species corresponds to the Diplodinium-type, pattern shared with genera Diplodinium, Diploplastron, Eudiplodinium, Eremoplastron and Polyplastron. A brief review conducted highlights the difficulty of delimiting Metadinium species due to the morphological similarity among them.